The Effect Of Annealing Temperature On The Properties Of Thin Zno Films Deposited Using Microwave-Assisted Spray Pyrolysis System (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2024)
This research aims to determine the optimal annealing temperature for the production of ZnO thin films using the microwave-assisted spray pyrolysis method. In the ZnO growth process, a high microwave temperature was used, with a spray pressure of 20 kg/m2, a nozzle distance of 12 cm, 3 layers, a spray duration of 5 seconds, and a 1-minute interval between layers. Annealing temperature variations included 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, and 600°C. SEM results indicated that the best morphology was achieved at 400°C, with the smoothest and least cracked surface. EDX results showed the highest ZnO composition percentage at 450°C, which was 93.61%.The optical properties obtained from UV-Vis spectroscopy revealed the lowest absorption in the visible light wavelength range (400-700 nm) at an annealing temperature of 450°C. Furthermore, the highest transmittance and the lowest bandgap were observed at an annealing temperature of 450°C, measuring 90.77% and 3.00 eV, respectively. Crystal property analysis from XRD data revealed that all samples had a hexagonal wurtzite structure. The best crystal index was achieved at 450°C, with a value of 81.899%. Increasing the annealing temperature improved the crystal properties, as evidenced by a decreasing full width half maximum (FWHM) until 450°C, which was 0.476°.